The Correlation of Students’ Perceptions About Speaking Skills Demonstration Method With Learning Outcomes of English Subject in Binjai “Ex School” Tutoring - Mariana; Rudi Purwana (Pena Cendekia Insani, 2021)
The demonstration method is a way of presenting information in KBM by demonstrating how to do something with a clear visual explanation of the process. Students have different perceptions about the demonstration method delivered by the teacher. The purpose of the research was to determine the relationship between students' perceptions of the speaking skill demonstration method and the learning outcomes of English subjects at the